Uma interface em Python para automatização do dimensionamento de subestações elétricas - Deus, Gilberto Giuliano Alves de (Brasil, 2024)
A power substation is a facility with equipment and devices specialized in the transmission and distribution of energy, playing an essential role in efficiently delivering electricity to consumers. These installations specialize in modifying electrical current levels to facilitate more efficient transmission and ensure operability. However, substations can only play this role due to their structural components, such as transformers, switches, lightning rods, sectional switches, and the high degree of specificity of the electronic devices that control the system, such as software. Therefore, in this work, an interface was developed in Python programming language to automate sizing in electrical substations. As a result, it was possible to observe a platform that facilitates the sizing of the substation and prevents mathematical errors from occurring, as the calculations are carried out in the code in addition to the simplified presentation of information, both input, and output, allowing greater efficiency and effectiveness in substation sizing process.